Kinship effects in quasi-social parasitoids I: co-foundress number and relatedness affect suppression of dangerous hosts. (11th June 2020) - Abdi, Mohamed Khadar; Lupi, Daniela; Jucker, Costanza; Hardy, Ian C W
Abstract: Explanations for the highest levels of sociality typically invoke the concept of inclusive fitness. Sclerodermus, a genus of parasitoid hymenopterans, is quasi-social, exhibiting cooperative brood care without generational overlap or apparent division of labour. Foundress females successfully co-exploit hosts that are too large to suppress when acting alone and the direct fitness benefits of collective action may explain their cooperation, irrespective of kinship. However, cooperation in animal societies is seldom free of conflicts of interest between social partners, especially when their relatedness, and thus their degree of shared evolutionary interests, is low. We screened components of the life-history of Sclerodermus brevicornis for effects of varying co-foundress number and relatedness on cooperative reproduction. We found that the time taken to paralyse standard-sized hosts is shorter when co-foundress number and/or relatedness is higher. This suggests that, while females must access a paralysed host in order to reproduce, individuals are reluctant to take the risk of host attack unless the benefits will be shared with their kin. We used Hamilton's rule and prior data from studies that experimentally varied the sizes of hosts presented to congeners to explore how the greater risks and greater benefits of attacking larger hosts could combine with relatedness to determine the sizes of hosts that individuals are selected to attack as a public good. From this, we predict that host size and relatedness will interact to affect the timing of host paralysis; we test this prediction in the accompanying study.